Business development through digital marketing for the Pothil business - Siti Noor Khikmah; Imam Agus Fauzi; Anggia Riama; Aprilia Kusuma Dewi; Aziza Daning Fitrilia; Salma Shafiyya Ayu Mutiarani (Community Empowerment, 2023)
The purpose of this community service is to increase digital marketing knowledge and skills for pothil MSME actors so they can develop their business. This program method consists of several stages, namely observation, outreach, digital marketing training, and mentoring. The result of this training is that MSMEs already have Facebook (Pothilinaja) and Instagram (Pothilin_aja) accounts which can be used to market their products widely.